ANALYSIS OF ADOLESCENT HEDONISTIC BEHAVIOR FROM THE PERSPECTIVE OF ISLAMIC CONSUMPTION THEORY IN LANGSA CITY - Maulina Ulfanur; Andriyani; Juli Dwina Puspitasari (Fakultas Ekonomi dan Bisnis Universitas Malikussaleh, 2026)
The rise of hedonistic behavior among adolescents has become increasingly evident due to the influence of social media, consumer culture, and modern lifestyles. However, studies examining this phenomenon from the perspective of Islamic consumption theory among adolescents in Langsa City remain limited. This study aims to analyze the forms of hedonistic behavior among adolescents aged 19–22 years in Langsa City and to examine these behaviors based on Islamic consumption theory. This research employed a qualitative field research approach. Data were collected through observation, in-depth interviews, and documentation involving 10 informants selected using purposive sampling. The findings reveal that hedonistic behavior is reflected in adolescents' tendency to follow lifestyle trends, such as purchasing branded products, owning an iPhone as a symbol of social status, and prioritizing consumption oriented toward personal satisfaction and social recognition. From the perspective of Islamic consumption theory, these behaviors do not fully reflect the principles of balanced consumption, avoiding extravagance (israf), and prioritizing the welfare of oneself, one's family, and society through spending in the way of Allah. This study contributes to the literature by providing an analysis of adolescent hedonistic behavior within the framework of Islamic consumption theory in the local context of Langsa City, thereby offering a reference for strengthening Islamic consumption literacy among young people.Keywords: hedonism; Islamic consumption; adolescents; Langsa City.